Um estudo da eficiência relativa das taxas de sucesso e dos desempenhos no ranking universitário da folha de São Paulo (RUF) das Universidades Federais Brasileiras para o ano de 2015 - Sombra, Luana Claudio (2017)
The subject on education is considered of great relevance, once that only the access to knowledge is capable of providing the transformation of a society. In this context, public and private universities play a key role in the economic development of a nation. Therefore, the aim of this work is to study the relative efficiency of success rates and performances in the University of São Paulo (RUF) Ranking of Brazilian Federal Universities for the year 2015, through the establishment of a relationship between the inputs used and the results achieved by each institution. The empirical analysis of this study applies the Data Envelopment Analysis (DEA) technique, using the Variable Scale Returns (DEA - BCC) model, with an orientation to a product. Data from 55 Brazilian Federal Universities were used to execute the model. The results showed that 19 institutions are considered efficient. We also presented reference units or benchmarkings, which should serve as a parameter to direct the inefficient units in the quest for efficiency.